The Influence of Internal Factors and Interest Rates on State-Owned Enterprise Credit Distribution - Gusanto, Priskilla Annetta Amanda; Sakti, Rachmad Kresna (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to analyze the effect of internal bank factors and Loan interest rates on credit distribution of state-owned banks in Indonesia during the period 2020–2025. The study is motivated by the suboptimal credit growth in the post-Covid-19 period despite adequate banking liquidity and government fund placement policies. The variables include Loan interest rates, Loan to Deposit Ratio (LDR), Operating Expenses to Operating Income (BOPO), and Capital Adequacy Ratio (CAR) as independent variables, and credit distribution as the dependent variable. This research employs a quantitative approach using the Autoregressive Distributed Lag (ARDL) model based on monthly time series data obtained from the Financial Services Authority (OJK). The long-run estimation results indicate that Loan interest rates have a positive and significant effect on credit distribution, while LDR and BOPO have a negative and significant effect. Meanwhile, CAR has a negative but insignificant effect. These findings suggest that in the long run, operational efficiency and liquidity management are key determinants of credit distribution, while capital adequacy is not a dominant factor. This study is expected to provide insights for policymakers and banking institutions in formulating more effective strategies to enhance financial intermediation and support economic recovery.